The impact of subdivision and sedentarization of pastoral lands on wildlife in an African savanna ecosystem - Western, D.; Groom, R.; Worden, J. (Elsevier, 2009)
This study looks at the impact of Subdivision and sedentarization of pastoral lands on wildlife numbers and production in a savanna ecosystem of southern Kenya. The study uses aerial counts over a period of 33 years to compare changes in wildlife populations on two adjacent and ecologically similar Maasai group ranches. During the period under study, one group ranch was subdivided and settled. The other remained communally owned under shifting seasonal use. Wildlife populations decreased sharply on the privatized ranch following subdivision and increased steadily on the adjacent ranch where pastoralists continued mobile pastoralism. The results of multivariate analysis show that Sedentarization and settlement distribution accounts for wildlife declines on the subdivided ranch. Both the direct displacement of wildlife and the reduction in grass production following a switch from seasonal to permanent grazing associated with sedentarization are discussed as causes of wildlife loss. Given the demand for title deeds among astoralists to counter land losses, the resulting sedentarization is likely to become the biggest threat to wildlife in the East African savannas.